Flamelet chemistry model for efficient axisymmetric counterflow flame simulations with realistic nozzle geometries and gravitational body force. Issue 5 (2nd September 2020) - Solmaz, Evrim; Bisetti, Fabrizio
Abstract : A flamelet model is applied to the simulation of axisymmetric counterflow laminar flames including gravitational acceleration and the geometrical details of main nozzles and annular shrouds. The flamelet chemistry model consists of two mixture fractions and is found to be very accurate when compared to results obtained with finite rate chemistry and mixture-average transport. Steady and unsteady solvers are implemented within the OpenFOAM framework. We perform simulations of pressurised counterflow flames for which experimental results are available. Further, we discuss key numerical aspects, including the prescription of robust boundary conditions that ensure steady solutions in the presence of buoyancy effects, the convergence rates of the residuals, issues related to mesh refinement, and the parallel performance of the steady and unsteady solvers. Finally, we apply the framework to a parametric study on the dependence of the counterflow flame on the governing dimensionless groups, i.e. Reynolds and Richardson numbers, and select boundary conditions. The simulations are efficient and enable parametric sweeps with little computational effort.